An inguinal hernia of the ovary and fallopian tube due to nonclosure of the canal of Nuck in a 9-month-old infant: A case report - Zaynab Iraqi; Khadija Belcadi; Nadia Mebrouk; Loubna Chtouki; Siham El Haddad; Nazik Allali; Bouchra Chkirat; Latifa Chat (Radiology Case Reports)
Herniation of the ovaries represents a rare congenital condition that can lead to complications such as strangulation, torsion, and potential infertility. We report the case of a 9-month-old female infant with no significant medical history, who presented with a right inguinal swelling. Abdominopelvic ultrasound confirmed a hernia containing the ovary and fallopian tube. The infant underwent surgical treatment with a good outcome. This case underscores the importance of early detection, clinical expertise, and judicious use of imaging, particularly ultrasound, to ensure a favorable prognosis in infants with ovarian hernias.